Multi-wave cohort study of sedentary work and risk of ischemic heart disease - Simone V Møller; Harald Hannerz; Aase Marie Hansen; Hermann Burr; Andreas Holtermann (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVES: This study aimed to investigate whether sedentary work is a distinct risk factor for ischemic heart disease (IHD) when the effect of occupational sitting is disentangled from that of occupational physical activity. METHODS: Data on occupational sitting time and several covariates were derived from the Danish Work Environment Cohort Study (DWECS) conducted every five years from 1990-2005 among the active Danish population. This study was designed as a multi-wave longitudinal study including participants employed at entry. Respondents were followed in national registers, first for death or hospital treatment due to IHD and second for purchase of medication that may prevent IHD from (re)occurring serving as a proxy for IHD. RESULTS: During 145 850 person-years of follow-up, 510 cases of fatal and non-fatal IHD occurred. After adjustment for age, sex, body mass index (BMI), and socioeconomic status, no difference in risk of IHD was observed between sedentary and non-sedentary employees [hazard ratio (HR) 0.95, 95% confidence interval (95% CI) 0.78-1.16]. During 44 949 and 42 456 person-years of follow-up among men and and women, respectively, 1263 men and 1364 women purchased IHD-related medication. No differences in risk were observed between sedentary and non-sedentary participants, either for men or women. A dose-response relationship between occupational sitting time and the risk of IHD was also not detected. CONCLUSIONS: This study could not confirm the hypothesis that sedentary work is a distinct risk factor for IHD. Future studies may further investigate the association with objective measures of occupational sitting time.